PRECLINICAL STUDIES OF KEFIR PRODUCT WITH REDUCED ALLERGENICITY OF Β-LACTOGLOBULIN - Korzhov R.P. (Foods and Raw Materials, 2015)
The most promising approach for reducing the allergenicity of milk products with high biological value is biocatalytic conversion of whey proteins, producing hydrolysates with the specified molecular-mass distribution and residual allergenicity. The purpose of this study was to evaluate the biological effect of kefir product produced with the use of whey protein hydrolysate. The experimental works were conducted at the A.N. Bach Institute of Biochemistry of Russian Academy of Sciences. The objects of the studies were males of Brown Norway rats of BN/SsNolaHsd line with RT1 haplotype with initial mass of about 150 g, which had been obtained from the centre for Laboratory Animal Breeding of Harlan Laboratories, Inc. Company and had passed quarantine for at least 3 weeks after delivery. A model for testing the bio-functional properties of fermented milk products on the basis of enzymatic whey protein hydrolysates was created. Its essence lies in the induction of IgE-mediated allergic reaction to antigens of dairy products by oral administration with adjuvant - chlorea toxin that increases the permeability of the intestinal wall. Multiple investigations on laboratory animals found that the developed kefir product, produced with the use of whey protein hydrolysate, is characterized by hypotensive, hypolipidemic and hypocholesterolemic effect compared to kefir produced by traditional technology, as well as by reduced allergenicity of β-lactoglobulin. According to the opinion of the Scientific Research Institute of Nutrition of the Russian Academy of Medical Sciences a status of diet (preventive) food product for adults with symptoms of food allergy to milk proteins was assigned to the fermented milk drink.